Genomic characterization and probiotic potential of Lactobacillus casei IDCC 3451 isolated from infant faeces. (9th February 2021) - Shin, M.; Ban, O‐H.; Jung, Y.H.; Yang, J.; Kim, Y.
Abstract: Probiotics play an important role in health benefits on the host. However, they also possess potentials for infectivity or in situ toxin production; thus, requiring a comprehensive assessment of their safety. In this study, we report genomic characteristics of a newly isolated Lactobacillus casei IDCC 3451 from infant faeces. Phenotypic assays based on enzyme activities and carbohydrate fermentation profiles represented metabolic features of the strain. Safety evaluation for antimicrobial resistance, biogenic amines production and cytotoxicity to a murine mouse model suggested its safe use as a probiotic strain. Our findings on the genetic background of L. casei IDCC 3451 and its potential features provide a promising functional and safe probiotic strain for the human consumption. Abstract : Significance and Impact of the Study: Supplementation of probiotics has rapidly increased because of their various health benefits. However, given the large quantities of probiotics consumed around the world, possible opportunistic infections are concerned, requiring a comprehensive assessment of their safety. This study characterizes genomic properties and evaluates safety‐associated phenotypic features of a newly isolated Lactobacillus casei IDCC 3451 from infant faeces. Our findings provide its potential use as a safe probiotic strain for the human consumption, demanding in‐depth functional mechanistic studies in human.